Probing densified silica glass structure by molecular oxygen and E’ center formation under electron irradiation - Ollier, N.; Reghioua, I.; Cavani, O.; Mobasher, M.; Alessi, A.; le Floch, S.; Skuja, Linards (Nature Research, 2023)
This study aims to learn more about the structure of densified silica with focus on the metamict-like silica phase (density = 2.26 g/cm3) by examining the formation of E’ point defects and interstitial molecular oxygen O2 by 2.5 MeV electron irradiation. High-dose (11 GGy) irradiation creates a metamict-like phase and a large amount of interstitial O2, which is destroyed upon subsequent additional lower-dose electron irradiation. The O2 cathodoluminescence (CL) data indicate that the formation of O2 from peroxy linkages Si–O–O–Si in silica network is strongly dependent on the intertetrahedral void sizes. The position and shape of the O2 emission line support the idea that the configuration of these voids in metamict phase is close to that of non-densified silica. Moreover, data support the strong correlation between the formation of 3-membered rings of Si–O bonds and E’-centers when silica density increases from 2.20 to 2.26 g/cm3. © 2023, Springer Nature Limited.
N. O sincerely thank G. Jullian de la Fuente for the help in data analysis during his free time. We are grateful to D. Neuville for his density measurements device. In addition, the Master 2 students I. Brahimi and A. Mouhoub are acknowledged also for their contribution to EPR measurements at high temperature. The authors acknowledge support from the EMIR&A French network (FR CNRS 3618) on the platform SIRIUS. L.S. acknowledges support by Latvian Science Council project lzp2021/1-0215.
Keywords: Research Subject Categories::NATURAL SCIENCES